Določanje kritične obremenitve krožnih kolobarjev v elasto-plastičnem območju - Bremec, Boštjan (Strojniški vestnik, 2002)
This paper presents an experimental determination of the buckling load and the buckling coefficient of a circular annular plane with constant thickness that is made of an elastic-plastic hardening material. The annulus is simply supported and uniformly loaded on the outer edge, the inner edge is free and not loaded. The unstable state appears when the stress state is already in the elastic-plastic domain. The experimental results are compared to the results obtained from a mathematical model, which can take into account an idealized elastic, linear hardening, rheological model or a measured stress-strain curve. The paper describes the measuring procedure, the equipment and the choice of the material and the geometry of the specimens, which ensure that elastic-plastic buckling occurs during the experiment. The difference between the experimental and numerical results is 5.5%.
Keywords: kolobarji krožni; območja elastoplastična; obremenitve kritične; metode eksperimentalne; krožni kolobarji; obremenitev; preizkušanje; elastoplastična deformacija